Sodium-ion battery electrolyte and sodium-ion battery
By leveraging the synergistic effect of modified graphite materials and composite additives, the stability and environmental adaptability issues of sodium-ion battery electrolytes have been resolved, achieving high efficiency, safety, and low-cost production of the battery, and improving its cycle life and safety performance.
Patent Information
- Application Number
- CN202511078330.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-01
- Publication Date
- 2025-12-12
AI Technical Summary
Existing sodium-ion battery electrolytes suffer from poor intrinsic electrolyte stability and weak environmental adaptability, resulting in high production costs and short battery cycle life, making it difficult to meet commercialization requirements.
Modified graphite materials are used to form a three-dimensional network structure with dopamine and polyethyleneimine, combined with Sb2O3 and BiCl3 doping, and specific composite additives to form a stable electrolyte interface film, thereby optimizing the electrolyte composition to enhance the safety and stability of the battery.
It improves the thermal and electrochemical stability of the electrolyte, suppresses side reactions at the electrode-electrolyte interface, extends battery cycle life, reduces production costs, and is adaptable to a wide temperature range.
Smart Images

Figure BDA0005530061100000131 
Figure BDA0005530061100000141
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium ion technology, specifically to a sodium ion battery electrolyte and a sodium ion battery. Background Technology
[0002] With the accelerated shift of the energy structure towards clean energy, the large-scale application of renewable energy sources such as wind and solar power has created an urgent need for efficient energy storage technologies. While commercially available lithium-ion batteries currently offer advantages such as high energy density and long cycle life, their development faces resource bottlenecks: global lithium reserves account for only 0.0065% of the Earth's crust, with 70% concentrated in South America. Furthermore, the reliance on expensive transition metals like cobalt for cathode materials results in high costs, making it difficult to meet the economic requirements for large-scale energy storage. In contrast, sodium-ion batteries, due to abundant sodium resources (2.3% of the Earth's crust), wide distribution, and a cost only one-third that of lithium-ion batteries, are widely recognized as the next-generation energy storage technology with the greatest industrialization potential.
[0003] Electrolytes, as the "blood" of battery systems, directly determine the safety and electrochemical performance of batteries. Currently, sodium-ion battery electrolytes still follow the traditional lithium-ion battery technology route, mainly using electrolytes such as sodium hexafluorophosphate and sodium perchlorate, which are sensitive to water and oxygen. These electrolytes have obvious drawbacks: (1) Sodium hexafluorophosphate is easily hydrolyzed to produce hydrofluoric acid, which corrodes the electrodes; (2) Sodium perchlorate has strong oxidizing properties, posing a risk of deflagration; (3) It needs to be prepared in an ultra-low water and oxygen environment of <0.1ppm, which greatly increases production costs. Although the existing technology uses a sulfolane / ionic liquid system to adjust the electrolyte composition, it fails to fundamentally solve the core problems of poor intrinsic stability and weak environmental adaptability of electrolytes, which seriously restricts the commercialization process of sodium-ion batteries. Therefore, developing a new electrolyte system that combines high safety, wide temperature range adaptability, and low cost has become a key breakthrough for promoting the large-scale application of sodium battery technology. Summary of the Invention
[0004] The purpose of this application is to provide a sodium-ion battery electrolyte and a sodium-ion battery, which have the advantages of improving electrolyte stability, enhancing electrode interface compatibility, and reducing production costs.
[0005] This invention provides a sodium-ion battery electrolyte, the technical solution of which is as follows:
[0006] The raw materials for preparing electrolytes include: electrolytes, organic solvents, and composite additives.
[0007] The raw materials for preparing electrolytes include sodium salts and modified graphite.
[0008] The raw materials for preparing modified graphite include: graphite, dopamine, polyethyleneimine, Sb₂O₃, and BiCl₃.
[0009] The composite additives include trimethylsilyl trifluoromethanesulfonate, N-methylpyrrolidone, vinylene carbonate, and nano-silica.
[0010] Sodium-ion battery electrolytes commonly use sodium hexafluorophosphate or sodium perchlorate. These materials are sensitive to water and oxygen environments, easily hydrolyzing to produce corrosive substances or posing a risk of deflagration. Traditional electrolyte systems require strict control of the water and oxygen content in the production environment to below 0.1 ppm, resulting in high production costs. Existing improvements have addressed the issue by adjusting organic solvents or adding stabilizers, but these have failed to effectively solve the problem of poor intrinsic electrolyte stability. Decomposition reactions still occur in high-temperature or humid environments, affecting battery cycle life and safety. To address these issues, this invention analyzes the interlayer sodium ion transport mechanism of graphite materials, discovering that traditional graphite materials lack an effective protective layer on their surface, leading to the continuous accumulation of electrolyte decomposition products during cycling. Further research revealed that constructing a three-dimensional coating structure on the graphite surface can simultaneously enhance ion conductivity and chemical stability. Based on this, dopamine and polyethyleneimine were selected as composite modifiers, combined with metal oxide doping to form a synergistic protective layer. Simultaneously, to meet the requirements of electrolyte interface film formation and free radical elimination, a combination of composite additives with specific functional groups was screened.
[0011] Therefore, this application proposes a sodium-ion battery electrolyte, the raw materials of which include an electrolyte, an organic solvent, and a composite additive. The electrolyte is composed of a sodium salt and modified graphite, which is prepared by reacting graphite with dopamine, polyethyleneimine, Sb₂O₃, and BiCl₃. The composite additive includes trimethylsilyl trifluoromethanesulfonate, N-methylpyrrolidone, vinylene carbonate, and nano-silica.
[0012] Modified graphite refers to a material formed by reacting oxidized flake graphite sequentially with dopamine hydrochloride and branched polyethyleneimine to form a polydopamine-polyethyleneimine composite coating layer, followed by doping modification with Sb₂O₃ and BiCl₃. This structure forms a dense coating layer through the self-polymerization reaction of dopamine, enhances the interlayer sodium ion diffusion channels through the branched structure of polyethyleneimine, and improves the Lewis acidity of the material surface by doping with Sb₂O₃ and BiCl₃, thus inhibiting electrolyte decomposition. In the composite additives, trimethylsilyl trifluoromethanesulfonate acts as a preferential reducing component, forming a uniform SEI film on the negative electrode surface. N-methylpyrrolidone lowers the sodium ion desolvation barrier through its strong solubilizing ability, vinylene carbonate scavenges reactive oxygen free radicals in the electrolyte, and nano-silica regulates the electrolyte viscosity through surface hydroxyl adsorption.
[0013] Specifically, the polydopamine-polyethyleneimine composite layer forms a three-dimensional network structure on the graphite surface, and its abundant amino functional groups can anchor sodium ions and promote rapid migration. During the modification process, Sb₂O₃ and BiCl₃ form an Sb-O-Bi bond structure, which exhibits strong Lewis acidity and preferentially adsorbs free fluoride ions in the electrolyte, blocking the hydrolysis chain reaction of sodium salts such as sodium hexafluorophosphate. Trimethylsilyl trifluoromethanesulfonate in the composite additive preferentially decomposes before carbonate solvents during the first charge and discharge, forming a dense SEI film rich in inorganic fluorides, effectively inhibiting the continuous decomposition of solvent molecules. Nano-silica reduces electrolyte fluidity through physical adsorption and forms a gel-like barrier layer when the battery overheats, delaying the thermal runaway process. Compared with existing technologies, traditional electrolytes relying on sodium hexafluorophosphate require the electrolyte injection process to be completed in a glove box. This solution, through the Lewis acid characteristics of modified graphite and the synergistic effect of the composite additives, enables the electrolyte to remain stable in environments with a water content below 50 ppm. The sulfolane solvent system used in the existing technology has a high viscosity at low temperatures, which leads to a decrease in ionic conductivity. However, the combination of N-methylpyrrolidone and nano-silica in this solution can maintain the stability of the electrolyte rheological properties in the range of -20℃ to 60℃.
[0014] Through the above technical solution, this invention achieves stable preparation of the electrolyte system under conventional production conditions, eliminates the risk of deflagration of perchlorate, and significantly improves battery cycle stability through interfacial film formation and free radical scavenging mechanisms. The three-dimensional coating structure of modified graphite increases the sodium ion diffusion coefficient by an order of magnitude, and the synergistic effect of composite additives improves the capacity retention of the electrolyte after high-temperature storage.
[0015] Furthermore, the present invention also proposes that the organic solvent includes at least one of ethylene carbonate and trimethyl phosphate.
[0016] Ethylene carbonate refers to an organic solvent with a cyclic carbonate structure, specifically industrial-grade products with a purity higher than 99.9%. Its high dielectric constant promotes sodium salt dissociation and enhances the electrolyte's ion transport capacity. Trimethyl phosphate refers to an organic solvent containing phosphoxy groups, specifically reagent-grade products that have undergone dehydration treatment. Its low viscosity reduces electrolyte flow resistance, and the coordination of sodium ions by the phosphoxy groups inhibits side reactions. Specifically, ethylene carbonate forms a dense and stable solid electrolyte interfacial film on the electrode surface through the strong coordination of the carbonyl group with sodium ions, thereby reducing interfacial impedance and inhibiting the continuous decomposition of the electrolyte. Trimethyl phosphate reduces system viscosity and increases flash point, allowing the electrolyte to maintain fluidity at low temperatures while avoiding safety hazards caused by solvent evaporation at high temperatures. The combined application of these two solvents can balance the electrochemical stability and safety of the electrolyte. For example, trimethyl phosphate can be used alone to improve fluidity at low temperatures, or a mixture of ethylene carbonate and trimethyl phosphate can be used at high temperatures to balance film-forming performance and thermal stability. Compared to existing technologies, traditional sodium-ion battery electrolytes typically use either propylene carbonate or trimethyl phosphate as solvents. Propylene carbonate's high viscosity leads to low-temperature performance degradation, while trimethyl phosphate's lack of effective film-forming components causes interfacial side reactions. This proposed solution, through an optimized combination of solvents, retains the film-forming advantages of ethylene carbonate while introducing trimethyl phosphate to improve kinetic performance, and simultaneously avoids the corrosion risk to electrode materials associated with traditional phosphate solvents.
[0017] Furthermore, the present invention also proposes that the sodium salt includes one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, sodium tetrafluoroborate, and sodium dioxoborate.
[0018] Sodium trifluoromethanesulfonate is a sodium salt containing trifluoromethanesulfonate ions. It can be prepared by the neutralization reaction of trifluoromethanesulfonic acid with sodium compounds. Its strong hydrophobic groups can block the contact between water and electrolytes. Sodium bis(fluorosulfonyl)imide is a sodium salt containing bisfluorosulfonylimide anions. It can be obtained by reacting fluorosulfonylimide with a sodium source. Its delocalized charge structure can reduce the resistance to sodium ion migration. Sodium tetrafluoroborate is a salt formed by tetrafluoroborate ions and sodium ions. It can be generated by reacting boric acid, hydrofluoric acid, and sodium salts. Its weak coordination properties help stabilize the electrode interface. Sodium bis(oxo)borate is a compound in which oxalic acid bicoordinated borate ions are combined with sodium ions. It can be prepared by reacting oxalic acid, boric acid, and a sodium source. Its chelating effect can passivate the active sites on the electrode surface. Specifically, sodium trifluoromethanesulfonate forms a physical barrier through hydrophobic groups to inhibit hydrolysis and acid production; sodium bis(fluorosulfonyl)imide reduces lattice energy and improves ion conduction efficiency through delocalized charge; sodium tetrafluoroborate promotes the formation of a stable solid electrolyte interface film through weak coordination; and sodium dioxoborate covers the highly active region of the electrode surface through chelation. The combination of these four sodium salts regulates the solvation structure of the electrolyte at the molecular level. Sodium trifluoromethanesulfonate and sodium dioxoborate synergistically inhibit electrode corrosion, while sodium bis(fluorosulfonyl)imide and sodium tetrafluoroborate jointly optimize the sodium ion transport pathway, thus forming a complementary stabilization mechanism. Compared with existing technologies, traditional sodium hexafluorophosphate electrolytes are prone to hydrolysis in humid environments, generating hydrofluoric acid that corrodes the current collector, while sodium perchlorate poses a risk of thermal runaway due to its strong oxidizing properties. The sodium trifluoromethanesulfonate used in this scheme did not release any acidic substances during the 60℃ damp heat test. Sodium dioxoborate can form a dense passivation layer in the potential range above 1.5V. Sodium tetrafluoroborate still maintains liquid conductivity at -20℃. Sodium bis(fluorosulfonyl)imide increases the electrolyte conductivity to above 12mS / cm.
[0019] Furthermore, the present invention also proposes that, by weight, the raw materials for preparing the electrolyte include: 0.5 to 5 parts of electrolyte, 85 to 95 parts of organic solvent, and 1 to 10 parts of composite additive.
[0020] The electrolyte is a conductive material composed of sodium salt and modified graphite. The sodium salt provides the sodium ion transport carrier, while the modified graphite enhances conductivity and interfacial stability through surface modification. The organic solvent is a liquid medium used to dissolve the electrolyte and form ion transport channels, such as ethylene carbonate or trimethyl phosphate; its proportion controls the electrolyte viscosity and electrochemical stability. The composite additive is a mixture of trimethylsilyl trifluoromethanesulfonate, N-methylpyrrolidone, vinylene carbonate, and nano-silica, which synergistically achieves electrode surface passivation and dendrite suppression. Specifically, the amount of electrolyte is limited to 0.5 to 5 parts to ensure sufficient carrier concentration for sodium ion transport while avoiding side reactions or increased preparation costs caused by excessive sodium salt. The organic solvent accounts for 85 to 95 parts as the main component of the electrolyte, maintaining suitable solution viscosity and ion migration efficiency through a high proportion. The composite additive, introduced at a ratio of 1 to 10 parts, effectively suppresses electrode interface side reactions at low dosages through a multi-protective mechanism formed by the film-forming effect of trimethylsilyl trifluoromethanesulfonate, the solvation regulation of N-methylpyrrolidone, the polymerization coating of vinylene carbonate, and the physical barrier of nano-silica. Compared with existing technologies, traditional sodium-ion battery electrolytes use more than 10% sodium salt content to maintain conductivity, resulting in excessively high electrolyte cost and a high risk of thermal runaway. This solution reduces the sodium salt content to below 5%, combined with the synergistic interface regulation function of the composite additive, significantly reducing material costs while maintaining conductivity. In existing technologies, additives often use a single component and exceed 15% in dosage. This solution controls the total amount of additives to below 10% through the synergistic effect of multiple components, reducing material consumption and avoiding the impact of excessive additives on electrolyte stability.
[0021] Furthermore, the present invention also proposes a method for preparing modified graphite comprising:
[0022] A1. After oxidizing flake graphite, it is reacted with dopamine hydrochloride, and then reacted with branched polyethyleneimine to obtain polydopamine-polyethyleneimine modified graphite oxide.
[0023] A2. Modified graphite is obtained by reacting polydopamine-polyethyleneimine modified graphite oxide with Sb2O3 and BiCl3.
[0024] Furthermore, the present invention also proposes that the temperature of the mixing reaction be 50–60°C.
[0025] Flake graphite oxidation treatment refers to the introduction of oxygen-containing functional groups onto the graphite surface through chemical oxidation. Specifically, a mixed solution of concentrated sulfuric acid and potassium permanganate can be used. This process increases the active sites on the graphite surface, providing a reaction basis for subsequent organic molecule modification. Dopamine hydrochloride reaction utilizes the self-polymerization properties of dopamine under weakly alkaline conditions. Specifically, a Tris buffer solution can be used to adjust the pH to 8.5-9.0 for the reaction. The resulting polydopamine layer enhances the interfacial compatibility between graphite and electrolytes through amino and phenolic hydroxyl groups. Branched polyethyleneimine reaction involves the formation of a three-dimensional network structure through intermolecular cross-linking. This can be achieved by constant-temperature stirring at 60°C in an aqueous solution. This structure can inhibit interlayer exfoliation of graphite and improve mechanical strength. The Sb₂O₃ and BiCl₃ mixed reaction involves in-situ composite formation at a specific temperature. Specifically, a hydrothermal reaction at 50-60°C can be used. The synergistic doping of Sb³⁺ and Bi³⁺ can regulate the electronic structure of graphite, while the composite phase of metal oxide and chloride can passivate side reactions on the electrode surface.
[0026] Specifically, a functionalized graphite matrix was constructed through a stepwise modification and composite modification strategy. After oxidation, oxygen-containing functional groups formed on the surface of flake graphite, providing anchoring sites for dopamine self-polymerization. The polydopamine layer enhanced interfacial bonding through amino and phenolic hydroxyl groups, while branched polyethyleneimine further crosslinked to form a three-dimensional network, inhibiting interlayer delamination of graphite. Subsequently, Sb₂O₃ and BiCl₃ combined with the modified graphite in a thermal reaction. Sb³⁺ and Bi³⁺ formed stable ion channels through electronic structure regulation, while the metal compound composite phase formed a protective layer on the graphite surface, suppressing electrolyte decomposition side reactions. This preparation method achieves simultaneous improvement in the structural stability and ion transport efficiency of graphite materials through organic-inorganic synergistic modification. Compared with existing technologies, traditional graphite modification often uses single organic coatings or metal oxide doping, which cannot simultaneously solve the problems of interlayer delamination and interfacial side reactions. For example, while existing technologies using polyacrylic acid to modify graphite can improve dispersibility, they lack a mechanically supportive structure; adding Sb₂O₃ alone can improve conductivity, but it does not solve the interfacial instability caused by metal particle agglomeration. This solution utilizes the synergistic effect of a polydopamine-polyethyleneimine three-dimensional network and an Sb-Bi bimetallic compound to maintain the integrity of the graphite structure while forming a uniform and stable ion transport interface.
[0027] Through the above technical solutions, this application effectively improves the thermal and electrochemical stability of the electrolyte, suppresses the occurrence of side reactions at the electrode-electrolyte interface, and enhances the transport efficiency of sodium ions in the graphite matrix. At high temperatures, the metal oxide composite phase can prevent electrolyte decomposition and gas generation; during cycling, the three-dimensional network structure can buffer volume changes and prevent the active material from pulverizing and shedding, thereby extending battery cycle life and improving safety performance.
[0028] Furthermore, the present invention also proposes that the mass ratio of flake graphite to dopamine hydrochloride is 1:(0.2-0.6):(0.1-0.2).
[0029] Flake graphite refers to carbon materials with a layered structure, specifically made from natural or artificial graphite. Its surface is oxidized to expose hydroxyl and carboxyl functional groups. Dopamine hydrochloride is an organic compound containing catechol groups and amino groups, which can form a polydopamine layer on the graphite surface through self-polymerization. Polyethyleneimine is a branched polymer containing a large number of amino groups, specifically made with a linear or hyperbranched structure with a molecular weight of 600-10000. Its amino groups react with the quinone groups in polydopamine through a Schiff base reaction to form a cross-linked network. Specifically, by controlling the mass ratio of flake graphite to dopamine hydrochloride within the range of 1:0.2–0.6, dopamine is uniformly polymerized on the graphite surface to form a continuous coating layer with a thickness of 5–20 nanometers. When the mass ratio is below 0.2, the coating layer is too thin to effectively isolate the direct contact between the electrolyte and the graphite; when the mass ratio is above 0.6, excess dopamine causes interparticle bridging and agglomeration. The addition ratio of polyethyleneimine was further limited to 1:0.1–0.2, utilizing the primary and secondary amine groups in its branched structure to crosslink with the o-benzoquinone groups in polydopamine, forming a three-dimensional network structure. This crosslinking density was controlled at 3–5 crosslinking points per square nanometer, maintaining both the mechanical strength of the modified layer and sufficient porosity for sodium ion transport. Compared to existing technologies, traditional graphite modification methods typically employ a single polymer, such as polydopamine or polyethyleneimine. Such single-modification layers suffer from uneven thickness and weak interfacial adhesion, making them prone to peeling during charge-discharge processes.
[0030] Furthermore, the present invention also proposes that the mass ratio of polydopamine-polyethyleneimine modified graphite oxide, Sb2O3, and BiCl3 is 1:(0.2-0.3):(0.2-0.3).
[0031] Among them, polydopamine-polyethyleneimine modified graphite oxide refers to a composite material formed by reacting oxidized flake graphite sequentially with dopamine hydrochloride and branched polyethyleneimine. Its surface amino functional groups can coordinate with metal salts. Antimony trioxide is a catalytically active metal oxide that promotes the insertion / extraction reaction of sodium ions. Bismuth trichloride is a metal salt containing heterogeneous elements that can reduce the interlayer diffusion barrier of graphite. The mass ratio is set to 1:0.2-0.3:0.2-0.3, ensuring that the metal salt does not cause particle agglomeration due to excess while providing sufficient active site density. Specifically, when polydopamine-polyethyleneimine modified graphite oxide is used as the substrate material, the surface amino functional groups fix antimony trioxide and bismuth trichloride nanoparticles through coordination bonds. Under the mass ratio of 1:0.2-0.3:0.2-0.3, the catalytic effect of antimony trioxide and the doping effect of bismuth trichloride synergistically form a uniformly dispersed composite system. This ratio allows the metal salt particles to reach a single-layer coverage threshold on the substrate surface, maintaining the continuity of the conductive network while optimizing the transport path of sodium ions through heterogeneous elements.
[0032] Furthermore, the present invention also proposes that, by weight ratio, trimethylsilyl trifluoromethanesulfonate, N-methylpyrrolidone, vinylene carbonate and nano-silica are 2-5:1-3:0.5-2:0.5-2.
[0033] Trimethyltrifluoromethanesulfonate is a silane compound containing a trifluoromethanesulfonic acid group. It can be prepared by chemical synthesis, where the trifluoromethanesulfonic acid group is grafted onto a trimethylsiloxane skeleton via a silanization reaction. In this method, it inhibits the oxidative decomposition of the electrolyte by adsorbing onto the positive electrode surface.
[0034] N-methylpyrrolidone refers to a polar aprotic solvent with pyrrolidone as the parent nucleus, specifically prepared by the condensation reaction of cyclopentanone and methylamine. In this method, it promotes sodium ion migration by controlling the solvation layer structure.
[0035] Vinylene carbonate refers to a cyclic carbonate compound containing vinyl groups, specifically prepared by reacting ethylene carbonate with a vinyl reagent. In this process, it preferentially reduces to form a stable solid electrolyte interfacial film.
[0036] Nano-silica refers to silica particles with a particle size at the nanoscale, which can be prepared using the sol-gel method or vapor deposition method. In this approach, surface hydroxyl groups improve the wettability of the electrolyte to the electrode.
[0037] Specifically, trimethylsilyl trifluoromethanesulfonate preferentially adsorbs onto the surface of the positive electrode material in the range of 2-5 parts, suppressing side reactions between the electrolyte and the high-potential positive electrode through steric hindrance. N-methylpyrrolidone dissolves the sodium salt in a ratio of 1-3 parts and regulates the solvation structure, improving migration efficiency by lowering the sodium ion desolvation energy barrier. Vinylene carbonate participates in the reduction reaction on the negative electrode surface in the range of 0.5-2 parts, forming an SEI film structure with a gradient distribution. Nano-silica forms a hydrogen bond network with electrolyte components through surface hydroxyl groups in the range of 0.5-2 parts, while optimizing electrode pore wetting through the physical filling of nanoparticles. The four components work synergistically under specific ratios: trimethylsilyl trifluoromethanesulfonate inhibits positive electrode oxidation, N-methylpyrrolidone stabilizes ion transport, vinylene carbonate regulates interfacial film formation, and nano-silica optimizes interfacial contact, collectively improving the stability of the electrolyte system. Compared to existing technologies, traditional electrolyte additives often employ single components or simple blends, such as using only vinylene carbonate as a film-forming agent or silica as a single thickener. These approaches suffer from overlapping or missing functionalities among components, leading to insufficient interfacial film mechanical strength or impaired ion transport. This solution, by precisely defining the ratio of four components, allows each additive to perform its targeted function in different regions of the electrode, while avoiding abnormal viscosity increases or particle agglomeration caused by excessive addition.
[0038] Furthermore, the present invention also proposes that the raw materials for preparing sodium-ion batteries include the sodium-ion battery electrolyte described above.
[0039] Modified graphite refers to a composite material formed by surface modification of graphite with dopamine and polyethyleneimine, combined with Sb₂O₃ and BiCl₃ doping. Specifically, it can be achieved by reacting graphite oxide with dopamine hydrochloride, grafting branched polyethyleneimine, and then mixing and reacting it with Sb₂O₃ and BiCl₃. This structure enhances the conductive network and sodium storage capacity of graphite, while improving the interfacial stability of the electrolyte. The composite additive is a mixture of film-forming agent, wetting agent, decomposition inhibitor, and mechanical reinforcing agent, specifically a mixture of trimethylsilyl trifluoromethanesulfonate, N-methylpyrrolidone, vinylene carbonate, and nano-silica in a specific ratio. This combination synergistically forms a stable SEI film and inhibits electrolyte decomposition. The sodium salt is a compound that provides a sodium ion transport carrier, specifically one or more of sodium trifluoromethanesulfonate and sodium bis(fluorosulfonyl)imide. This component promotes sodium ion migration through high dissociation. Specifically, in the electrolyte system, sodium salt and modified graphite work together as the electrolyte. Sodium salt dissociates to provide sodium ions, while modified graphite enhances the stability of the electrode interface through a surface-modified three-dimensional conductive network. Simultaneously, the doping of Sb₂O₃ and BiCl₃ further optimizes the sodium storage performance of graphite. In the composite additives, trimethylsilyl trifluoromethanesulfonate forms a uniform SEI film on the negative electrode surface, N-methylpyrrolidone improves the wettability of the electrolyte to the electrode, vinylene carbonate inhibits the oxidative decomposition of the electrolyte, and nano-silica enhances the mechanical strength of the electrolyte through physical filling. The organic solvents chosen are ethylene carbonate or trimethyl phosphate; the former promotes sodium salt dissociation, while the latter provides flame-retardant properties. Through the synergistic effect of the components, the electrolyte significantly improves its antioxidant properties and thermal stability while maintaining high ionic conductivity. Compared to other technologies, traditional sodium-ion battery electrolytes use sodium hexafluorophosphate or sodium perchlorate as electrolytes, which suffer from easy hydrolysis and acid production, poor thermal stability, and require preparation in an ultra-low water-oxygen environment. This solution reduces the amount of water- and oxygen-sensitive sodium salt by replacing part of the sodium salt with modified graphite. Simultaneously, the nano-silica and trimethylsilyl trifluoromethanesulfonate in the composite additives synergistically inhibit electrolyte decomposition, allowing the electrolyte to be prepared in a conventional production environment. Furthermore, the synergistic doping of Sb₂O₃ and BiCl₃ endows the modified graphite with both high sodium storage capacity and structural stability, overcoming the rapid capacity decay of traditional graphite in sodium-ion batteries.
[0040] Through the above technical solutions, this application solves the problem of short battery cycle life caused by poor intrinsic stability of electrolytes, reduces the stringent requirements of the electrolyte production environment, and simultaneously inhibits electrolyte decomposition through the synergistic effect of composite additives, thereby improving battery safety under high-temperature conditions. The synergistic use of modified graphite and sodium salt further optimizes the electrode / electrolyte interface stability, enabling the battery to maintain stable electrochemical performance over a wide temperature range.
[0041] As can be seen from the above, the sodium-ion battery electrolyte and sodium-ion battery provided in this application effectively improve the ion conduction efficiency of the electrolyte and form a stable solid electrolyte interface film by using a graphite material synergistically modified with polydopamine-polyethyleneimine and a specific composite additive system. This has the advantages of improving electrolyte stability, enhancing electrode interface compatibility, and reducing production costs. Detailed Implementation
[0042] The following will describe the concept and technical effects of the present invention clearly and completely with reference to the embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.
[0043] Example 1
[0044] This embodiment provides an electrolyte comprising an electrolyte, an organic solvent, and a composite functional additive. The electrolyte is composed of sodium trifluoromethanesulfonate and modified flake graphite in a mass ratio of 10:3. The electrolyte accounts for 3% of the electrolyte's mass fraction, and the composite functional additive accounts for 5% of the electrolyte's mass fraction. The organic solvent is composed of ethylene carbonate, trimethyl phosphate, adiponitrile, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether in a mass ratio of 40:30:25:15.
[0045] The composite functional additive is composed of trimethylsilyl trifluoromethanesulfonate, N-methylpyrrolidone, vinylene carbonate and nano-silica in a mass ratio of 2:1:2:1.
[0046] The method for preparing the modified flake graphite includes the following steps:
[0047] (1) Immerse 20.0g of flake graphite (325 mesh) in 500mL of 5% KMnO4 aqueous solution, add 50mL of concentrated H2SO4, and react at 55±2℃ for 4 hours. After the reaction is completed, terminate the reaction with 5% H2O2 solution, centrifuge and wash until pH=6-7 to obtain graphite oxide (GO);
[0048] (2) Disperse 10.0g GO in 500mL Tris-HCl buffer (pH=8.5), add 5.0g dopamine hydrochloride, stir magnetically at 25℃ (600rpm) for 12 hours, collect PDA@GO by centrifugation, resuspend PDA@GO in 200mL deionized water, add 3.0g branched PEI (Mw=25kDa), react in a water bath at 60℃ for 3 hours, and dialysis purification (MWCO=10kDa) for 24 hours to obtain PDA-PEI@GO.
[0049] (3) 10.0g PDA-PEI@GO, 2.5g Sb2O3, and 2.5g BiCl3 were ultrasonically dispersed in 300mL of ethanol / water (7:3v / v) mixed solvent (40kHz, 300W) for 1 hour, stirred in an oil bath at 60℃ for 4 hours (N2 protection), and vacuum dried (60℃, 12h) to obtain the final modified product.
[0050] Example 2
[0051] This embodiment provides an electrolyte comprising an electrolyte, an organic solvent, and a composite functional additive. The electrolyte is composed of sodium trifluoromethanesulfonate and modified flake graphite in a mass ratio of 12:3. The electrolyte accounts for 5% of the electrolyte by mass, and the composite functional additive accounts for 3% of the electrolyte by mass. The organic solvent is composed of ethylene carbonate, trimethyl phosphate, adiponitrile, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether in a mass ratio of 50:25:20:5.
[0052] The composite functional additive is composed of trimethylsilyl trifluoromethanesulfonate, N-methylpyrrolidone, vinylene carbonate and nano-silica in a mass ratio of 3:2:1:1.
[0053] Example 3
[0054] This embodiment provides an electrolyte comprising an electrolyte, an organic solvent, and a composite functional additive. The electrolyte is composed of sodium trifluoromethanesulfonate and modified flake graphite in a mass ratio of 8:3. The electrolyte accounts for 2% of the electrolyte by mass, and the composite functional additive accounts for 8% of the electrolyte by mass. The organic solvent is composed of ethylene carbonate, trimethyl phosphate, adiponitrile, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether in a mass ratio of 35:35:20:10.
[0055] The composite functional additive is composed of trimethylsilyl trifluoromethanesulfonate, N-methylpyrrolidone, vinylene carbonate and nano-silica in a mass ratio of 1:2:3:2.
[0056] The difference between this embodiment and Example 1 is that the Sb2O3 / BiCl3 ratio in the preparation of modified flake graphite is adjusted to 3:2.
[0057] Example 4
[0058] This embodiment provides an electrolyte comprising an electrolyte, an organic solvent, and a composite functional additive. The electrolyte is composed of sodium trifluoromethanesulfonate and modified flake graphite in a mass ratio of 15:3. The electrolyte accounts for 6% of the electrolyte's mass fraction, and the composite functional additive also accounts for 6% of the electrolyte's mass fraction. The organic solvent is composed of ethylene carbonate, trimethyl phosphate, adiponitrile, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether in a mass ratio of 40:35:15:10.
[0059] The composite functional additive is composed of trimethylsilyl trifluoromethanesulfonate, N-methylpyrrolidone, vinylene carbonate and nano-silica in a mass ratio of 4:3:1:1.
[0060] Comparative Example 1
[0061] This comparative example provides a sodium-ion battery electrolyte. The difference between this comparative example and Example 1 is that the dopamine hydrochloride in Example 1 is replaced with o-phenylenediamine, while the other conditions are the same.
[0062] Comparative Example 2
[0063] This comparative example provides a sodium-ion battery electrolyte. The difference between this comparative example and Example 1 is that the polyethyleneimine in Example 1 is replaced with polyacrylamide, while the other conditions are the same.
[0064] Comparative Example 3
[0065] This comparative example provides a sodium-ion battery electrolyte. The difference between this comparative example and Example 1 is that Sb2O3 in Example 1 is replaced with indium chloride, while the other conditions are the same.
[0066] Comparative Example 4
[0067] This comparative example provides a sodium-ion battery electrolyte. The difference between this comparative example and Example 1 is that trimethylsilyl trifluoromethanesulfonate in Example 1 is replaced with ethyl trifluoromethanesulfonate, while the other conditions are the same.
[0068] Test case
[0069] Sodium-ion batteries were prepared using the electrolytes obtained in the above examples and comparative examples, respectively, according to the following methods.
[0070] The positive electrode of a sodium-ion battery: Na 0.9 Cu 0.22 Fe 0.3 Mn 0.48 O2 is the positive electrode material, and Na is the positive electrode material. 0.9 Cu 0.22 Fe 0.3 Mn 0.48 O2, carbon nanotubes (CNTs) and polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 97.4:1.3:1.3, coated onto an aluminum foil current collector, dried in an oven, and rolled on a roller press to obtain the desired positive electrode sheet.
[0071] The negative electrode of a sodium-ion battery: hard carbon is selected as the negative electrode material. Hard carbon, sodium carboxymethyl cellulose (CMC), carbon nanotubes (CNTs), and styrene-butadiene rubber (SBR) are mixed evenly in a ratio of 95.8:1.4:0.8:2.0, coated on an aluminum foil current collector, dried in an oven, and rolled on a roller press to obtain the required negative electrode sheet.
[0072] The separator for sodium-ion batteries is a ceramic-coated polyethylene (PE) membrane with a thickness of 2μm ceramic + 12μm PE + 2μm ceramic.
[0073] The electrodes were stacked to form a 2Ah small pouch battery. The electrolytes of the example and comparative examples were added to test the performance. The test results are shown in Table 1 below.
[0074] The prepared batteries were subjected to cycle tests at 45°C and -10°C. The batteries were charged to 4.0V at 0.5C and then left to rest for 5 minutes; subsequently, they were discharged to 1.5V at 0.5C and left to rest for 5 minutes. This process was repeated 400 times to obtain the battery capacity after 400 cycles when discharged to 1.5V at 0.1C. The capacity retention rate was calculated using the following formula: Capacity retention rate = (400th cycle discharge capacity / First cycle discharge capacity) × 100%.
[0075] Table 1 Performance Tests
[0076]
[0077]
[0078] In Comparative Example 1, replacing dopamine hydrochloride with o-phenylenediamine reduced the surface coverage of the o-phenylenediamine polymerization product by 37%, resulting in fewer anchoring sites for Sb / Bi nanoparticles during cycling and accelerating the shedding of active materials. Secondly, the lack of catechol's antioxidant protection accelerated the decomposition rate of the electrolyte at high potentials. Under low-temperature conditions, the binding energy between unprotected oxygen-containing functional groups on the modified graphite surface and sodium ions increased, leading to increased Na+ ionization. + The increased desolvation barrier can lead to interfacial failure processes, resulting in an abnormal increase in SEI film thickness. This ultimately manifests as increased charge transfer impedance and increased low-temperature polarization voltage during cycling at 45°C.
[0079] In Comparative Example 2, replacing branched polyethyleneimine with polyacrylamide led to a decrease in high-temperature cycling and low-temperature performance. The linear PAA contained only primary amino groups and had poor molecular chain flexibility, which reduced the anchoring efficiency of Sb / Bi nanoparticles. Secondly, the linear structure of PAA could not construct effective ion channels, ultimately resulting in an increase in charge transfer impedance and a reversible capacity loss at -10℃ after 400 cycles.
[0080] In Comparative Example 3, firstly, In has poor plastic deformation ability, which causes electrode particle cracks during cycling, accelerates the rupture and regeneration of the SEI film, and leads to a decline in the performance of Comparative Example 3.
[0081] Comparative Example 4 shows that high-temperature cycling accelerates the formation of unstable SEI, ultimately leading to a decrease in capacity retention at 45°C and a reduction in discharge efficiency at -10°C.
[0082] Comparative Example 5 lacks the passivation effect of trimethylsilyl trifluoromethanesulfonate on aluminum foil, which leads to an increase in the corrosion current of the current collector, resulting in an aggravation of side reactions at a high temperature of 45°C, an inability to maintain a stable interface structure, and a decline in performance.
[0083] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A sodium-ion battery electrolyte, characterized in that, The raw materials for preparing the electrolyte include: electrolyte, organic solvent, and composite additives. The raw materials for preparing the electrolyte include sodium salt and modified graphite. The raw materials for preparing the modified graphite include: graphite, dopamine hydrochloride, polyethyleneimine, Sb₂O₃, and BiCl₃. The composite additives include trimethylsilyl trifluoromethanesulfonate, N-methylpyrrolidone, vinylene carbonate, and nano-silica.
2. The sodium-ion battery electrolyte according to claim 1, characterized in that, The organic solvent includes at least one of ethylene carbonate and trimethyl phosphate.
3. The sodium-ion battery electrolyte according to claim 1, characterized in that, The sodium salt includes one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, sodium tetrafluoroborate, and sodium dioxoborate.
4. The sodium-ion battery electrolyte according to claim 1, characterized in that, The raw materials for preparing the electrolyte, by weight, include: 0.5 to 6 parts of electrolyte, 85 to 95 parts of organic solvent, and 1 to 10 parts of composite additive.
5. The sodium-ion battery electrolyte according to claim 1, characterized in that, The method for preparing the modified graphite includes: A1. After oxidizing flake graphite, it is reacted with dopamine hydrochloride, and then reacted with branched polyethyleneimine to obtain polydopamine-polyethyleneimine modified graphite oxide. A2. Modified graphite is obtained by reacting polydopamine-polyethyleneimine modified graphite oxide with Sb2O3 and BiCl3.
6. The sodium-ion battery electrolyte according to claim 5, characterized in that, The temperature of the mixing reaction is 50–60°C.
7. The sodium-ion battery electrolyte according to claim 5, characterized in that, The mass ratio of the flake graphite to dopamine hydrochloride is 1:0.2-0.6:0.1-0.
3.
8. The sodium-ion battery electrolyte according to claim 5, characterized in that, The mass ratio of the polydopamine-polyethyleneimine modified graphite oxide, Sb2O3, and BiCl3 is 1:0.2-0.3:0.2-0.
3.
9. The sodium-ion battery electrolyte according to claim 5, characterized in that, The trimethylsilyl trifluoromethanesulfonate, N-methylpyrrolidone, vinylene carbonate and nano silica are in a weight ratio of 2-5:1-3:0.5-2:0.5-2.
10. A sodium-ion battery, characterized in that, The raw materials for preparing the sodium-ion battery include the sodium-ion battery electrolyte as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Solid electrolyte filled with graphene composite cladding material and preparation method thereof
CN110429331A
Electrolyte and sodium ion battery
CN115621557A
Cited By
Preparation method of high-wear-resistance hard alloy for underground mine
CN121653448A